CASP-Model Sepsis Triggers Systemic Innate Immune Responses Revealed by the Systems-Level Signaling Pathways - Ai, Hannan; Li, Bizhou; Meng, Fanmei; Ai, Yuncan (Frontiers in Immunology, 2022)
The colon ascendens stent peritonitis (CASP) surgery induces a leakage of intestinal contents, which may cause polymicrobial sepsis related to post-operative failure of remote multi-organs (including kidney, liver, lung and heart) and possible death from systemic syndromes. Mechanisms underlying such phenomena remain unclear. This article aims at elucidating mechanisms underlying the CASP-model sepsis through analyzing real-world GEO data (GSE24327_A, B and C) that were generated from spleen at 12 hours after the CASP-surgery in septic MyD88-deficient and wildtype mice, respectively, compared with untreated wildtype mice. Firstly, we identify and characterize 21 KO MyD88-associated signaling pathways, on which true key regulators (including ligands, receptors, adaptors, transducers, transcriptional factors and cytokines) are marked, which were coordinately, significantly, differentially expressed at the systems-level, thus providing massive potential biomarkers that warrant experimental validations in the future. Secondly, we observe the full range of polymicrobial (viral, bacterial and parasitic) sepsis triggered by the CASP-surgery through comparing the coordinated up- or down-regulations of true regulators among the experimental treatments borne by the three data under study. Finally, we discuss the observed phenomena of “systemic syndrome”, “cytokine storm” and “KO MyD88 attenuation”, as well as the proposed hypothesis of “spleen-mediated immune-cell infiltration”. Together, our results provide novel insights into a better understanding of innate immune responses triggered by the CASP-model sepsis in both wildtype and MyD88-deficient mice at the systems-level in a broader vision, which may serve as a model for human, to guide ultimately formulating research paradigms and composite strategies for the early diagnosis and prevention of sepsis.